2019
DOI: 10.13189/ujer.2019.071409
|View full text |Cite
|
Sign up to set email alerts
|

The Influence on the Style of Teaching in Entrepreneurship Courses: A Study on Lecturer Against Students' Interest in Entrepreneurship

Abstract: Entrepreneurial concern matters to the Government of Indonesia. One way of the Government to make its citizens into self-employment by implementing entrepreneurship courses at the College. Entrepreneurship courses currently exist in various departments not only the Department of management and business alone but for all the majors taught entrepreneurship courses. As key in order for students attending entrepreneurship being an entrepreneur is a lecturer at the faculty. This research was to look at the influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Banfield's research [39] found that there are no statistically significant differences in learning motivation that can be attributed to the type of teacher and teacher behavior, ranging from appropriate to inappropriate. By contrast, the lecturer has an important role in increasing student interest [40].…”
Section: Discussionmentioning
confidence: 99%
“…Banfield's research [39] found that there are no statistically significant differences in learning motivation that can be attributed to the type of teacher and teacher behavior, ranging from appropriate to inappropriate. By contrast, the lecturer has an important role in increasing student interest [40].…”
Section: Discussionmentioning
confidence: 99%
“…While Saeed (2015), Trivedi (2016) and Gujrati et al (2019) underscored the influence of institutions of higher learning as enablers and providers of entrepreneurial training, extant studies have turned out mixed results concerning the influence of faculties. Studies (Olokundun, 2017;Sukandi et al, 2019) have submitted that skill, experience and teaching methods used by the faculties play a significant role in increasing students' interest towards becoming entrepreneurs. Conversely, Diegoli et al (2018) found that teachers experience in entrepreneurship has no significant impact on the students' entrepreneurial intentions.…”
Section: Predictors Of Entrepreneurial Intentionsmentioning
confidence: 99%